IMPLEMENTASI SISTEM KEARSIPAN DIGITAL DI MADRASAH TSANAWIYAH: STUDI KASUS ADAPTASI TEKNOLOGI INFORMASI DALAM PENGELOLAAN DOKUMEN PENDIDIKAN - Az Zahro, Fatimah; Wahidin; Taufik Ismail, Achmad; Fajar Hadiansyah, Charil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the transformation of digital archiving systems in Madrasah Tsanawiyah in Cirebon City, as well as analyzing the obstacles and opportunities in the implementation of digital archiving management in Islamic educational institutions. This research was conducted using a qualitative case study approach, supplemented with in-depth interviews, to uncover current practices and challenges in archiving related to digital transformation, as well as projected solutions. It was found that the madrasah has a hybrid system, combining physical and digital archives, with several issues related to document organization/arrangement, storage location, and digital storage security. The madrasah has organized a structured folder system and uses cloud-based storage, and has begun the process of document scanning. The challenges faced include limitations in technological infrastructure and concerns regarding the security of electronically stored data. This study concludes that successful digital archive transformation requires a robust backup system and a phased transition strategy with technological innovation. The study provides insights into digital transformation patterns in Islamic educational institutions and practical recommendations for similar institutions aiming to modernize their archives.